Euphorbia mongoliensis (Euphorbiaceae), a new species from Inner Mongolia, China - Zang, Er-Huan; Zhang, Ming-Xu; Wang, Wen-Le; Zhang, Chun-Hong; Li, Min-Hui (Phytotaxa, 2021)
In May 2020, a new taxon of Euphorbia, Euphorbiaceae was collected from a dry hillside of Dongsheng District, Ordos City, Inner Mongolia. The morphological characteristics of the specimens analyzed differ from those of the known Euphorbia species from this region; therefore, we suspected this may be a new species, and we set to analyze the ITS2 sequences of some Euphorbia species. The results show that the new taxon belongs to the sect. Esula of Euphorbia subg. Esula. It is similar to Euphorbia esula (description from Flora of China) but does not belong to the same species. Concomitantly, plant morphological data and pollen morphology results show significant differences between the new taxon, E. esula and E. caesia, a finding that supports the delimitation of this new taxon, which is named Euphorbia mongoliensis in accordance with its geographical distribution.